The influence of knee and ankle bracing on lower extremity kinetics and kinematics during jogging - Campbell, B. M.; Armstrong, C. W.; Cipriani, D.; Yaggie, J. A. (ISB Congress, 2005)
The purpose of this investigation was to determine how ankle bracing alone, knee bracing alone, and ankle and knee bracing together affect lower extremity kinetics and kinematics during straight ahead jogging in healthy subjects.